THE EFFECT OF ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE TROUGH ENTREPRENEURIAL COMPETENCE IN CULINARY SECTOR MSMEs - Sonia Adelya; Louis Utama (Graduate Program of Universitas Tarumanagara, 2026)
This study was conducted with the aim of examining the effect of entrepreneurial orientation on business performance with entrepreneurial competence as a mediating variable among MSME culinary business actors in North Jakarta. The research design applied was quantitative approach. The sampling method used was non-probability sampling with purposive sampling technique, which is the selection of respondents based on certain criteria, such as culinary business actors who have been operating for at least one year and are included in the MSME category. This study involved 100 respondents who were culinary MSME entrepreneurs in North Jakarta. Data were obtained through direct questionnaire distribution and analyzed using the PLS SEM method with SmartPLS software. Before structural analysis was carried out, the research instruments were first tested for validity and reliability to ensure the accuracy and consistency of each indicator in measuring the variables under study. The results of the study show that entrepreneurial orientation has a positive and significant effect on business performance. In addition, entrepreneurial orientation also has a positive and significant effect on entrepreneurial competence, while entrepreneurial competence has a positive and significant effect on business performance. Furthermore, entrepreneurial competence has been proven to play a mediating role in the relationship between entrepreneurial orientation and business performance.